ANALISIS POLA PERTUMBUHAN EKONOMI ANTAR PROVINSI DI PULAU SULAWESI TAHUN 2015-2019 - Marsitha, Rizka; Saenong, Zainuddin; Matoka, Ulfa (Jurnal Ekonomi Pembangunan (JEP) UHO, 2023)
The purpose of this study was to determine differences in growth patterns between provinces on the island of Sulawesi based on the growth rate of GRDP and per capita income of each province. The data used is secondary data obtained from BPS publications which include: GRDP growth rate in 2015-2019 and per capita income in 2015-2019. The method of data analysis using Klassen Typology analysis. The results of Klassen's typology analysis show that the provinces of Central Sulawesi and South Sulawesi are included in the prosperous regions (quadrant I) because they have a high growth rate and per capita income compared to Sulawesi Island. Meanwhile, those included in (quadrant II) are the Provinces of North Sulawesi, Southeast Sulawesi. This area is also called a fast developing area because it has higher economic growth but lower per capita income level compared to Sulawesi Island. And those included in (quadrant IV) are the provinces of Gorontalo and West Sulawesi. This area is also called a relatively underdeveloped area because it has a lower growth rate and per capita income compared to Sulawesi Island.